Boys’ love, byte-sized: a qualitative exploration of queer-themed microfiction in Chinese cyberspace - Shaw, Gareth (2017)
This project undertakes an in-depth, qualitative investigation into queer-themed ‘Boys Love’ microfiction within the realm of Chinese cyberspace, with the aim of further understanding both the features of the genre and the motivation for production and consumption among its primarily heterosexual female user-base. Expanding upon previous studies, which have focused primarily on investigation into the consumer groups of such fiction, this project seeks to establish links between the linguistic/discursive features of queer Chinese-language microfiction and observable social phenomena or cultural frameworks.